A numerical analysis of near tip fields in a bending moment-loaded double cantilever sandwich beam fracture specimen - Burlayenko, V. N.; Sadowski, Tomasz; Pietras, Daniel (НТУ "ХПІ", 2018)
The paper presents an interfacial crack problem adopted for studying fracture toughness and debonding tolerance of sandwich composite materials. A specific example of the fracture sandwich specimens such as a double cantilever sandwich beam subjected to uneven bending moments (DCB-UBM) is considered. A finite element modelling of this test method is carried out using the ABAQUS™ code. Atwo-dimensional (2-D) model has been developed to highlight the distribution of stress and displacement fields and to calculate the energy release rate (ERR) and the phase angle at the interface crack between two dissimilar orthotropic materials. The J − integral approach built-in ABAQUS code and the crack surface displacement method programmed as an add-on subroutine within the Matlab® environment are used for computing those fracture parameters. The influence of different moment ratios on the near crack tip stress state, the ERR, and phase angle fracture parameters is estimated.

Представлено проблему міжфазної тріщини, за допомогою якої вивчаються в’язкість руйнування та стійкість до відшарування у тришарових композиційних матеріалах. Розглянуто конкретний приклад тришарового зразка на руйнування – двохконсольна тришарова балка, яка навантажена згинальними моментами. Скінчено елементне моделювання цього тесту здійснюється за допомогою програми ABAQUS™. Двовимірна модель була розроблена для виявлення розподілу полів напружень та переміщень, а також для розрахунку швидкості вивільнення енергії руйнування та фазового кута міжфазної тріщини поміж двома різними ортотропними матеріалами. J − інтеграл підхід, який є вбудованою опцією у ABAQUS, та метод відносних зміщень на поверхнях тріщини, який запрограмований у середовищі Matlab® окремою програмою, використовуються для обчислення цих параметрів руйнування. Оцінюється вплив різних співвідношень згинальних моментів на напружений стан в околі вершини тріщини, швидкості вивільнення енергії руйнування і фазовий кут.
Чисельний аналіз полів в околі вершини тріщини у двоконсольному балочному тришаровому зразку, що навантажений згинальними моментами
Keywords: bi-material interface; fracture parameters; finite element method; energy release rate; Crack Surface Displacement; інтерфейс біматеріалу; параметри руйнування; метод скінчених елементів